ASSA13-10-13 Cellular Repressor E1A-Stimulated Genes Controls Phenotypic Switching of Adventitial Fibroblasts by Blocking p38MAPK Activation. (29th April 2013) - Yang, Li; Jie, Tao; Jian, Zhang; Xiaoxiang, Tian; Shaowei, Liu; Mingyu, Sun; Xiaolin, Zhang; Chenghui, Yan; Yaling, Han
Abstract : Background: Phenotypic modulation of adventitial fibroblasts (AFs) plays an important role in the pathogenesis of proliferative vascular diseases. The current study aimed to identify the role of cellular repressor E1A-stimulated genes (CREG), a critical mediator in the maintenance of vascular homeostasis, in AF phenotypic modulation and adventitial remodelling. Methods: Two models of AF phenotypic modulation were used: the in vivo injury-induced adventitial remodelling and the in vitro Ang II-induced AF phenotypic modulation. CREG's function in AFs was investigated after over-expression of CREG with infection with adenovirus expressing full-length human CREG cDNA. Results: Using in situ double-immunofluorescence staining, we ascertained that CREG expression was significantly downregulated in the adventitia after vascular injury, and its expression pattern was conversely correlated with the expression of smooth muscle α-actin (α-SMA), a marker for differentiation of AFs into myofibroblasts. In vitro data confirmed the association of CREG in angiotensin II (Ang II)-induced AF differentiation. Additionally, over-expression of CREG attenuated Ang II-induced α-SMA expression in AFs. CREG over-expressing AFs showed decreased levels of proliferation on days 2 to 5 following stimulation by Ang II compared with controls, with changes in the cell cycle profile as shown by BrdU incorporation assay and fluorescence activated cell sorting analysis. Moreover, wound healing assay and transwell migration model demonstrated that upregulation of CREG expression inhibited Ang II-induced AF migration. We found that CREG mediated its counterbalancing effects in Ang II-induced phenotypic modulation, proliferation and migration by inhibition of the p38MAPK signalling pathway, validated by pharmacological blockade of p38MAPK with SB 203580 and by over-expression of p38MAPK with transfectants expressing constitutively active p38αMAPK. Conclusions: Our findings suggest that CREG is a novel AF phenotypic modulator in a p38MAPK-dependent manner. Modulating CREG on the local vascular wall may become a new therapeutic target against proliferative vascular diseases.